Anaerobic Fermentation of Rice Bran with Starter Liquid Organic Supplement (LOS) from Sheep Manure - Mahardika, Rayi Prima; Hernaman, Iman; Ayuningsih, Budi; Rosani, Urip (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
Fermented bran is an additive product which is an inoculum of lactic acid bacteria, which has been mixed with other ingredients and has gone through a fermentation process. This research aims to determine the effect of using sheep feces Liquid Organic Supplement (LOS) on fermented rice bran on lactic acid content, pH, dry matter loss, and Fleigh value (NF). The research was carried out on January 24 – February 14 at the Ruminant Animal Nutrition Laboratory, Faculty of Animal Husbandry, Padjadjaran University in Jatinangor Sumedang. The research used experimental methods with a Completely Randomized Design (CRD) with 3 treatments and 6 replications. Treatment consisted of P0 (1 kg bran: 300 g molasses), P1 (1 kg bran: 200 g molasses: 100 mL SOC) and P2 (1 kg bran: 100 g molasses: 200 mL SOC). The research data was processed using Variety Print Analysis and Duncan's Advanced Test. The results showed a significant effect (P<0.05) on lactic acid content, pH, dry matter loss, and Fleigh value. The conclusion of this research shows that the use of P2 treatment (1 kg bran: 100 g molasses: 200 mL LOS) can produce the best fermented bran.